Theory Analysis of Justice Against Good-faith Buyers in Freedom of Contract - Miarsa, Fajar Rachmad Dwi; Nasution, Krisnadi; Prasetyawati, Endang; Hadi, Syofyan (jfpublisher, 2022)
The Abuse of circumstances can occur when one of the parties has advantages in economic, psychological, and physical fields. The cases regarding the abuse of circumstances in Indonesia is often occur, but the law in Indonesia has not regulated this matter and is only based on jurisprudence. The case that often occurs is one of the parties who has weak economy in dependence/need position, then they forced to voluntary accept the clauses or promises made by monopolized party (bargaining power) in order to get the things needed (achievements), although the agreement can be detrimental to them. This research uses normative legal research which is also called doctrinal legal research. Normative legal research is legal research conducted by examining library materials or secondary legal data. Normative legal research is also called literature law research. The results of this research are good faith buyers who prioritize the main principle, no harm others and based on the principle of propriety as stated by Aristotle and Adam Smith.